Effects of polyethylene glycols on intestinal efflux pump expression and activity in Caco-2 cells - Darya Hodaei; Behzad Baradaran; Hadi Valizadeh; Parvin Zakeri-Milani (Universidade de São Paulo, 2015)
The present study was planned to investigate the influence of polyethylene glycols (PEGs) on the activity and expression of P-glycoprotein (P-gp). Sub-toxic concentrations of PEGs in Caco-2 cells were determined using the MTT test assay. Then the measurement of Rhodamine-123 (Rho-123) uptake, a P-gp fluorescence substrate, in Caco-2 cells confronting PEG 400 (1% and 2% w/v), PEG 4000 (2% and 4% w/v), PEG 6000 (2% and 4% w/v), PEG 10000 (2% and 4% w/v), PEG 15000 (1% and 2% w/v), and PEG 35000 (2% and 4% w/v) overnight was taken to elucidate whether non-toxic concentrations of PEGs are able to impact P-gp activity. Furthermore, western blotting was carried out to investigate P-gp protein expression. The results showed that PEG 400 at concentrations of 1% (w/v) and 2% (w/v) and PEG 6000 at the concentration of 4% (w/v) are notably capable of blocking P-gp. Based on the obtained results it is concluded that the mentioned excipients could be used to obstruct P-gp efflux transporter in order to increase the bioavailability of co-administered substrate drug.